People Management and Barriers to Innovation in Digital Transformation [Gestión de Personas y Las Barreras Para Innovar en la Transformación Digital] - Gonzalez-Candia, J; Mardones-Espinosa, M (Universidad del Zulia, 2021)
The article presents the main results of a study whose objective was to explain in an integrated way the main barriers that arise in the area of people management in Chilean companies to incorporate innovation and digital transformation. In methodological terms, a quantitative approach was used at a level, preferably descriptive. A survey was administrated to 91 company representatives using an intentional sampling criterion. The results identified the main barriers in the area of people management to innovate in the digital transformation, the most frequent innovation actions, the type of technology used in the processes, the degree of knowledge that the professionals in the area possess and the level of strategic positioning of the unit in these areas. It concludes that a new strategic approach is needed to the general management’s vision towards people management and a change in their functions, processes and services, and to use innovation and digitalization as success factors for digital transformation. © 2021, Universidad del Zulia. All rights reserved.